Universal three-body recombination and Efimov resonances in an ultracold Li-Cs mixture - Ulmanis, Juris; Häfner, Stephan; Pires, Rico; Werner, F.; Petrov, D. S.; Kuhnle, Eva; Weidemüller, Matthias (Physical review, 2016)
We study Efimov resonances via three-body loss in an ultracold two-component gas of fermionic 6Li and bosonic 133Cs atoms close to a Feshbach resonance at 843 G, extending results reported previously [Pires et al., Phys. Rev. Lett. 112, 250404 (2014)] to temperatures around 120 nK. The experimental scheme for reaching lower temperatures is based upon compensating the gravity-induced spatial separation of the mass-imbalanced gases with bichromatic optical dipole traps. We observe the first and second excited Li-Cs-Cs Efimov resonance in the magnetic field dependence of the three-body event rate constant, in good agreement with the universal zero-range theory at finite temperature [Petrov and Werner, Phys. Rev. A 92, 022704 (2015)]. Deviations are found for the Efimov ground state, and the inelasticity parameter η is found to be significantly larger than those for single-species systems.